How decisions lead to conflicts – The roles of elephant behaviour and agricultural practices in elephant crop consumption - Vogel, SM (2018)
Elephant crop consumption can have negative direct and indirect consequences for subsistence farmers (e.g. crop losses, livelihood vulnerability, fear) and can result in a reduction in support for the conservation of elephants, which are IUCN classified as vulnerable, and can even result into physical conflicts that can lead to injuries and death of people and elephants. In this thesis, I examine how decisions that elephants make in their movements and foraging behaviour, and farmers make in their mitigation methods, influence elephant crop consumption in the eastern panhandle of the Okavango Delta, Botswana. Chapter 2 shows that elephant corridors are important for exploratory movements of elephants towards the river, and that sexual segregation occurs in elephants’ responses to agricultural fields. Female elephants showed encamped movements in agricultural fields at night and during the dry season, supporting the predation-risk hypothesis, as crop consumption was safest for elephants at these times. Chapter 3 and Chapter 4 suggest that the local natural diet of elephants may be deficient in micronutrients – in particular phosphorus - which indicates that elephants need to consume large amounts of vegetation in order to satisfy their micronutrient levels. This makes crops an optimal alternative, due to their higher levels of absolute phosphorus and dry matter intake. Chapter 5 reveals that one-off inputs of materials to support farmers to deter elephants from their fields do not result in the sustainable mitigation method use desired by providers of materials. In order to empower farmers to live with elephants, external bodies such as government and non-governmental organisations could increase logistical support, and facilitate the improvement of the supply-chain of materials for mitigation methods. Crop consumption mitigation could be improved if sexual segregation in crop consumption patterns are taken into account and crops are harvested earlier (Chapter 2), if alternative micronutrient sources are provided in elephant corridors (Chapter 3 and Chapter 4) and farmers are included in the development and implementation of mitigation method interventions (Chapter 5). >